Yield of six grape varieties in Nuevo León - Manzanares-Miranda, Nelson; Villalón-Mendoza, Horacio; Malacara-Ramírez, Rosa Isela; Rocha-Domínguez, Luis; Garza-Ocañas, Fortunato; González-Delgado, Marisol (Revista Mexicana de Ciencias Agrícolas, 2025)
The vine (Vitis vinifera L.) is one of the oldest and most economically important crops in the world. Due to the relevance that this crop has taken on in Mexico and in the state of Nuevo León, in 2023, the proposed objective was to evaluate the yield of six grape varieties in the vineyard of the Center for Research in Agricultural Production of the Autonomous University of Nuevo León; the varieties used were Chardonnay, Chenin Blanc, Merlot, Cabernet Sauvignon, Malbec and Shiraz. For sampling, three plants per variety and 25 grapes per plant were taken and the weight of the production and the yield in kg ha-1 were evaluated. The total sugar content was evaluated using the variables of pH and degrees Brix. An analysis of variance (Anova) was performed considering a p-value ≤ 0.05. The results indicate significant differences in the variables of degrees Brix, pH and yield per hectare. Regarding degrees Brix, the Shiraz cultivar with an average of 26.5 and Chardonnay with 24.1 were the ones that showed the highest values. In terms of pH, the Shiraz cultivar presented the highest value (4.04) and Cabernet Sauvignon the lowest (3.46). The Malbec cultivar had the highest yield with 8 772.8 kg ha-1, followed by the Cabernet Sauvignon cultivar with 5 765.5 kg ha-1, so the study suggests that these vine varieties can be considered as an alternative crop for the southern region of the state of Nuevo León.